The Struggle of Indonesian-Americans to Speak Their Native Language in Shaping Their Identity - pristianto_adi, marcelliano_bagaskara (Language Horizon: Journal of Language Studies, 2025)
Indonesians have migrated to the United States for different purposes. Some initially arrived to pursue their studies and ended up staying after completing their education. Others migrated in search of improved job opportunities. While the first generation of immigrants still holds a strong connection to Indonesia, it remains uncertain whether their children feel the same sense of attachment to their ancestral homeland. The purpose of this research is aimed to understand the complexities of language maintenance within the Indonesian-American diaspora and the underlying factors influencing language use. This study employed qualitative research to gather insights from a diverse sample of Indonesian-Americans. The findings indicate that Indonesian-Americans encounter various challenges in sustaining their native language, including limited opportunities for language transmission, cultural assimilation, and the prevalence of English in their daily lives. Consequently, subsequent generations exhibit varying levels of language proficiency and connection to their Indonesian heritage. The struggle to preserve the native language raises implications for individual and collective identity, cultural preservation, and intergenerational communication. Based on the study's outcomes, recommendations include supporting language maintenance initiatives such as heritage language programs, community engagement, and leveraging digital resources to ensure the continued vitality and cultural richness of the Indonesian language within the Indonesian-American diaspora.